Barriers to and impacts of hepatitis C treatment among people who inject drugs in Kenya: A qualitative study. - Hannah N Manley; Lindsey R Riback; Mercy Nyakowa; Matthew J Akiyama; Peter Cherutich; John Lizcano; Ann Kurth; Abbe Muller (PLOS Global Public Health)
Hepatitis C (HCV) disproportionately affects people who inject drugs (PWID). Despite availability of safe and effective treatment, HCV treatment access and uptake among PWID in low- and middle-income countries (LMICs) has been limited. Understanding the lived experiences of PWID in these settings who have undergone treatment provides the opportunity to gain insight into how to implement treatment programs that meet the needs of this population. Using Rhodes' Risk Environment Framework to guide our work, we conducted semi-structured interviews with 35 PWID who received HCV treatment in methadone clinics and drop-in-centers (DICs) in Nairobi and coastal Kenya supported by peer case managers from August to September 2019. Translated and transcribed interviews were analyzed thematically. Three overarching themes emerged in our thematic analysis: 1) Financial constraints as a barrier to HCV treatment, 2) HCV-related stigma, and 3) HCV treatment impacts on health and risk behaviors. These data signal unique challenges faced by PWID seeking HCV treatment in this LMIC setting and highlight the importance of interventions to reduce barriers to treatment. In order for positive treatment outcomes to be sustained, HCV treatment programs must address the barriers patients face at multiple levels and implement system-level changes.